Analisis Pengaruh Diversifikasi Skripsi Terhadap Produktivitas Menulis Mahasiswa Program Studi Sistem Informasi UIN Sumatera Utara - Suendri; Santoso, Heri; Andriani, Mega (AI Society & STMIK Indonesia, 2022)
The form of the final project at the State Islamic University of North Sumatra, Medan is not only in the form of a thesis but can also be in the form of a journal article. Final thesis and journal articles have different forms, ranging from writing formats, templates, to the number of pages that must be completed. In terms of writing, students sometimes experience difficulties and obstacles ranging from difficulty finding data, running out of ideas, writer's block, discipline to unproductive writing. Therefore, to see the effect of journal articles as a substitute for thesis on student writing productivity, it is necessary to conduct research using three indicators, namely completion targets, processing time, and the number of references used. This study uses mix method research methods with data collection through questionnaires and literature study. After conducting research, which was based on productivity indicators, it was found that there was no effect of journal articles as a substitute for thesis on the writing productivity of each student.